Novel Kenanga Karya Oka Rusmini - Setya Yuwana Sudikan (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2006)
Abstract This article will analyze character in novel Kenanga by Oka Rusmini using Freudian hermeneutic theory. The method being used is interpretation with chose recitation. The result of the analysis finds that the technique of narration is in harmony and psychological conflict between the two characters Kenanga and Intan, is conspicuons. The inner conflict which is analysed by the use of Freudian hermeneutic (psychotext) which includes id, ego, and superego, neurosis anxicty and reality principles is appropriate to expose Kenanga and Intan’s way of thinking and inner condition when they are facing problems. In fact the two characters are not able to dolve the challenge offered by the problems. This makes readers easily understand the principle concept offered by Freudian hermeneutic theory through the novel Kenanga. Key words: Freudian hermeneutik, id, ego, superego.